(untitled) (Biological Sciences - PJSIR, 2024)
The production of bioplastics from banana peels instead of conventional petroleum-based plastics is seen as a successful solution to increase the efficiency of the plastics industry, at a lower cost than common plastics, lower carbon footprint and eco-safety. The project’s prototype represents the process of producing bioplastics from banana peels and tests the tensile strength shelf-life detection and efficiency of the produced plastic. The results showed that the plastic produced with the optimum resident time to hydrolysis was 15 min for the sample, the weight of bioplastic formed when adding (0.5 N) HCL and (0.5N) NaOH solutions was 5.6 g, while 3.8 g formed of bioplastic when adding (0.1 N) HCL and (0.3 N) NaOH. The best plastic formed in trial 4 with a weight of 17 g of paste, thin, light in colour, has elasticity and strength and did not show any signs of decay after 2 months. The worst trial we present in trial 5 plastic formed, which was thicker than in trials 2 and 3 and dark in colour, lost its strength, showed signs of decay after 1 month and the lowest weight of the paste in addition, the characterized and weight of bioplastic formed in trial 4 has 17 g of paste and was thin, light in colour and strength very strong, not shown any signs of decay after 2 months. The tensile strength for the neutral sample was 0.4086 N/mm2 at the residence for 15 min. It has been shown that bioplastic produced from banana peel contains many nutrients and The bioplastic product contains after lab analysis a high amount of the composition of the fiber, NPK, organic matter and C:N ratio. These results showed the bioplastic produced from banana peels which can be used as food packaging, plates, agricultural pots and soil fertilizer. It is concluded that the use of bioplastics will help in sustainability and is one of the most innovative environmentally friendly materials developed.